Generating web service request from annotated BPEL - Nguyen, Ngoc Son. (2009)
Business Process Execution Language (BPEL) has been popularly used to describe a collaborative business processes which is executed by Web services. However, the original BPEL language is defined in a strict format which the developers must follow. This leads to difficulties to create or modify the BPEL documents. In order to overcome the problem, the original BPEL has been extended to an Annotated-BPEL so that BPEL documents can be freely modified. One of the applications of Annotated-BPEL is that it is employed to describe “request” Web service information. Since Web service discovery systems may support different Web service description languages, Annotated-BPEL must be translated into specific description languages so that it can be readable and understood. This project introduces a system that generates “request” Web services from the Annotated-BPEL. This system supports the two most popular Web services description languages, namely, OWL-S and WSDL. The Annotated-BPEL is first translated into OWL-S since it contains semantics in describing the service. This work is done by searching ‘the best matched’ OWL concepts in an OWL repository and then filling these concepts matching into a predefined OWL-S template. If we cannot find any suitable concepts or the concept similarity of pair of matching concepts is not above some predefined thresholds, a WSDL document will be generated.